Fabrication of the Titanium dioxide nanowires on the FTO substrate and evaluating the efficiency power conversion in the dye-sensitized solar cell - Noura H. Haran; Qhatan A.Yousif (Al-Qadisiyah Journal of Pure Science, 2019)
The present work involves fabricating TiO2 nanowires on the fluoride doped Tin oxideglass substrate by the hydrothermalmethod to use as photoelectrode in the dye-sensitized solar cell together with a counter graphene nanoplatelets. The morphologyand structure of TiO2 nanowires were characterized by the scanning electron microscopy, X-ray diffraction, and energydispersive X-ray spectroscopy. The results emphasized the synthesis of it on the FTO at the optimum conditions such as degreeof temperature and reaction time. The photovoltaic parameters estimated and the solar cell showed the fill factor close to0.304under irradiated with a light source at 85 mW/cm2.